A study on reliable diagnosis of allergic respiratory diseases by using eosinophil count in nasal and blood smear: a prospective study in tertiary care centre - Ankireddy, Korisipati; M., Mallikarjuna (International Journal of Contemporary Pediatrics, 2019)
Background: Allergic rhinitis and asthma are two very common allergic diseases of respiratory tract in pediatric patients. In this geographical area, where the prevalence of allergens exists, the role of allergens as the etiological factor is higher in allergic respiratory disorders. Confirmation of allergen as etiologic agent is cumbersome in a small setup, where IgE estimation and allergy tests are not accessible. In this study, the simple test of peripheral smear and nasal smear eosinophil count as a reliable diagnosis to solve the above problem and establishing allergy as etiological agent has been tried. Methods: A present study which was conducted over 2 years in children between 2 to 12 years who visited tertiary health care centre, Kurnool medical college and general hospital. The allergic respiratory cases based on typical history and clinical features were included in the study and investigated for nasal and blood eosinophilia. Children with TB, recurrent and chronic pneumonia, malnutrition, malignancy, collagen vascular disorders and those who are on steroid therapy were excluded from the study. The clinical profile of allergic rhinitis with or without asthma and nasal and blood eosinophils are studied. Results: Out of 120 patients, there was male predominance and incidence was increasing as age increases. Dust is the most common risk factor for allergic rhinitis followed by weather changes, whereas in allergic rhinitis with bronchial asthma, weather change is common risk factor followed by dust and family history. Conclusions: In children with allergic rhinitis with or without bronchial asthma, there is positive relation between nasal and peripheral smear eosinophil count.